A literature review on environmental regulation and policy and quality assurance: A blueprint for the Malaysian food and beverage companies - Akanmu, M.D.; Bahaudin, Ahmad Yusni; Jamaludin, Roslan (UUM College of Business, 2016)
The main objective of this study is to develop a life cycle mode for a process-oriented quality assurance in organizational performance of food and beverage companies.As an iterative and dynamic process, quality assurance is interwoven in the developmental process of food and beverage companies.Through the review of literature s in existence, specifically those that focus on procedures, frameworks, methodology, a process oriented framework is developed around non-linear sequential stages presented as: planning/before, design and production (during), post production and delivery (after).The model is approved through an advanced systematic methods employed in collecting, organizing and generating reports about quality assurance (QA) needed updates or changes. According to the approach of process oriented lifecycle, many studies emphasizes that quality assurance needs a friendly environment that take quality as a key factor and a work value for attaining the objectives of an organization. A practical quality assurance model is then proposed by this study that complies with the guide of food and beverage development phases.In each stage of development, practical steps are recommended. There is great potential in the quality assurance model for its transformation from static, the state of after-the-fact to a state of dynamism and iterative state, thereby improving the ongoing self-improvement culture, rather than compliance of circumstance.